The relationship between emotional exhaustion and job embeddedness in nurses: the mediating role of decent work perception and the moderating role of job crafting - Xin, Dinuo; Xin, Dina; Bian, Meirong; Li, Wanling; Niu, Jinyan (Frontiers in Psychology, 2025)
ObjectivesNurse turnover is a global challenge facing healthcare systems, severely impacting the stability of nursing teams and the quality of care. Job embeddedness is a key predictor of nurse retention. This study aims to explore the relationship between nurses’ emotional exhaustion and job embeddedness and to analyze the mediating and moderating roles of decent work perception and job crafting in this relationship.MethodsThis was a multicenter cross-sectional study. From February to March 2025, an online questionnaire was administered to 653 nurses from three general hospitals in Shanxi Province, China, using convenience sampling. The questionnaire consisted of the Demographic Information Questionnaire, Emotional Exhaustion Scale, Decent Work Perception Scale, Job Crafting Scale, and Job Embeddedness Scale. The mediating and moderating effects were tested via the PROCESS Macro 4.1 (Model 4 and Model 5) of SPSS 27.0.ResultsThere was a significant negative correlation between nurses’ emotional exhaustion and job embeddedness (p < 0.001). Decent work perception played a partial mediating role between emotional exhaustion and job embeddedness, accounting for 44.1% of the total effect. In addition, job crafting positively moderated the effect of emotional exhaustion on job embeddedness.ConclusionBased on the results of this study, nursing managers should develop and adopt comprehensive and effective intervention strategies to reduce nurses’ emotional exhaustion, stimulate their level of decent work perception and job crafting to improve their job embeddedness, and ultimately stabilize the nursing workforce.